2013
DOI: 10.4161/nucl.27364
|View full text |Cite
|
Sign up to set email alerts
|

Implications of COMT long-range interactions on the phenotypic variability of 22q11.2 deletion syndrome

Abstract: (2013) Implications of COMT long-range interactions on the phenotypic variability of 22q11.2 deletion syndrome, Nucleus, 4:6,[487][488][489][490][491][492][493]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…Which other factors are necessary to result in abnormal phenotypes in ascertained individuals with these CNVs remains to be determined. It is possible that phenotypic similarity and variability of 22q11.2 CNVs may be impacted by dysregulation of genes via loss of long-range regulatory sequences that could affect either common genes and/or common developmental pathways [Yamagishi and Srivastava, 2003;Zeitz et al, 2013]. Indeed, Zeitz et al [2013] demonstrated long-range chromatin interaction of COMT in the proximal 22q11.2 region with genes on other chromosomes, as well as with MAPK1 in the distal 22q11.2 region, supporting this interpretation.…”
Section: Variability Of Phenotypesupporting
confidence: 69%
“…Which other factors are necessary to result in abnormal phenotypes in ascertained individuals with these CNVs remains to be determined. It is possible that phenotypic similarity and variability of 22q11.2 CNVs may be impacted by dysregulation of genes via loss of long-range regulatory sequences that could affect either common genes and/or common developmental pathways [Yamagishi and Srivastava, 2003;Zeitz et al, 2013]. Indeed, Zeitz et al [2013] demonstrated long-range chromatin interaction of COMT in the proximal 22q11.2 region with genes on other chromosomes, as well as with MAPK1 in the distal 22q11.2 region, supporting this interpretation.…”
Section: Variability Of Phenotypesupporting
confidence: 69%
“…CNVs are polymorphic and seen in the DGV database, however the frequency seen within our OAVS When analyzing the pathogenicity of the CNVs, we have identified reports of patients with OAVS features and CNVs within the Cat Eye region [54,55]. Moreover, chromosome 22q has been repeatedly reported in association with OAVS (2,(7)(8).…”
Section: Cnvs On 22q1121mentioning
confidence: 79%
“…In fact, the authors show that chromosomal rearrangements on 22q11 can have widespread effects on chromatin organization, and may contribute to the inherent phenotypic variability associated with those rearrangements [55]. The expression of genes on 22q might be disturbed during development by the presence of genomic imbalances (CNVs), increasing the susceptibility for OAVS craniofacial abnormalities.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…39 The phenotypic heterogeneity in 22q11.2DS might be because of (1) the various sizes of the deletions and/or (2) rearrangements elsewhere on the genome -especially CNVs, mutations in candidate genes and changes in the three-dimensional structure of the genome that can lead to dysregulation of gene expression. Zeitz et al 40 found that longrange interactions in the COMT gene had an impact on phenotypic variability. The use of aCGH only covers the CNVs and maps deletion breakpoints.…”
Section: Discussionmentioning
confidence: 99%